Tuberculosis in Australia's tropical north: a population-based genomic epidemiological study - Ella M Meumann, FRACP; Kristy Horan, PhD; Anna P Ralph, PhD; Belinda Farmer, MPH&TM; Maria Globan, BSc; Elizabeth Stephenson, MPH&TM; Tracy Popple, RN; Rowena Boyd, MAE; Mirjam Kaestli, PhD; Torsten Seemann, PhD; Koen Vandelannoote, PhD; Christopher Lowbridge, DrPH; et al. (Elsevier, 2021)
Background: The Northern Territory (NT) has the highest tuberculosis (TB) rate of all Australian jurisdictions. We combined TB public health surveillance data with genomic sequencing of Mycobacterium tuberculosis isolates in the tropical 'Top End' of the NT to investigate trends in TB incidence and transmission. Methods: This retrospective observational study included all 741 culture-confirmed cases of TB in the Top End over three decades from 1989-2020. All 497 available M. tuberculosis isolates were sequenced. We used contact tracing data to define a threshold pairwise SNP distance for hierarchical single linkage clustering, and examined putative transmission clusters in the context of epidemiologic information. Findings: There were 359 (48%) cases born overseas, 329 (44%) cases among Australian First Nations peoples, and 52 (7%) cases were Australian-born and non-Indigenous. The annual incidence in First Nations peoples from 1989-2019 fell from average 50.4 to 11.0 per 100,000 (P<0·001). First Nations cases were more likely to die from TB (41/329, 12·5%) than overseas-born cases (11/359, 3·1%; P<0·001). Using a threshold of ≤12 SNPs, 28 clusters of between 2-64 individuals were identified, totalling 250 cases; 214 (86%) were First Nations cases and 189 (76%) were from a remote region. The time between cases and past epidemiologically- and genomically-linked contacts ranged from 4·5 months to 24 years. Interpretation: Our findings support prioritisation of timely case detection, contact tracing augmented by genomic sequencing, and latent TB treatment to break transmission chains in Top End remote hotspot regions.